THE ROLE OF SOFT SKILLS IN THE DEVELOPMENT OF DEONTOLOGICAL COMPETENCE OF FUTURE EDUCATION TEACHERS (American Journal of Interdisciplinary Research and Development, 2024)
In the article, it is analyzed that pedagogical deontology represents a system of learning about certain ethical and moral laws for teachers. It also teaches the relationship between future education teachers and students, ethical principles implemented during the educational process, and how teachers should perform legal and moral management.